From bonding to belonging: The role of job satisfaction and decent working environment between sustainable coworker relations and turnover intention - Hasanein, Ahmed M.; Elrayah, Musaddag (International Journal of Innovative Research and Scientific Studies, 2025)
This study aims to investigate the effects of sustainable coworker relationships and decent working conditions on job satisfaction, organizational commitment, and turnover intention within the Saudi industrial sector. By exploring these associations, the research seeks to contribute to the growing body of knowledge on workplace sustainability and employee retention. Quantitative research design was employed, utilizing a modified questionnaire adapted from established literature. Data were collected from a randomly selected sample of 188 employees working in the Saudi industrial sector via an online survey developed using Google Forms. The collected data were analyzed using SMART-PLS version 4.0.1.1 and the Bootstrap method to test both direct and indirect associations among variables, with particular attention given to the mediating roles identified in the model. The results indicate that sustainable co-worker relationships have a significant positive impact on organizational commitment and perceptions of decent working conditions, while their direct effect on turnover intention was found to be insignificant. Moreover, mediation analysis demonstrated the positive and strengthening role of the mediators incorporated into the model, enhancing the relationships between independent and dependent variables. The study concludes that fostering sustainable coworker relationships and ensuring decent working conditions are critical factors for improving employee commitment and satisfaction in the Saudi industrial sector, although these factors may not directly reduce turnover intention without the presence of mediating mechanisms. The findings provide valuable insights for organizational leaders and human resource managers in the Saudi industrial sector, emphasizing the need to cultivate a supportive workplace culture and favorable working conditions. Strengthening co-worker relationships and workplace environments could enhance organizational commitment and job satisfaction, ultimately contributing to long-term organizational stability and performance.